2022
DOI: 10.1007/s00775-021-01922-3
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) and silver(I)-1,10-phenanthroline-5,6-dione complexes interact with double-stranded DNA: further evidence of their apparent multi-modal activity towards Pseudomonas aeruginosa

Abstract: Tackling microbial resistance requires continuous efforts for the development of new molecules with novel mechanisms of action and potent antimicrobial activity. Our group has previously identified metal-based compounds, [Ag(1,10-phenanthroline-5,6-dione)2]ClO4 (Ag-phendione) and [Cu(1,10-phenanthroline-5,6-dione)3](ClO4)2.4H2O (Cu-phendione), with efficient antimicrobial action against multidrug-resistant species. Herein, we investigated the ability of Ag-phendione and Cu-phendione to bind with double-strande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…AgNPs also induced DNA fragmentation in L. donovani promastigotes, as verified by the TUNEL technique; however, gel electrophoresis showed that DNA breakage was not extensive, indicating the presence of high-molecular-weight DNA fragments of 700 bp [ 44 ]. Interestingly, the treatment of P. aeruginosa with bactericidal concentrations of Cu-phendione induced DNA fragmentation [ 46 ]. Ag-phendione and Cu-phendione were able to bind to double-stranded DNA via hydrogen bonding, hydrophobic and electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AgNPs also induced DNA fragmentation in L. donovani promastigotes, as verified by the TUNEL technique; however, gel electrophoresis showed that DNA breakage was not extensive, indicating the presence of high-molecular-weight DNA fragments of 700 bp [ 44 ]. Interestingly, the treatment of P. aeruginosa with bactericidal concentrations of Cu-phendione induced DNA fragmentation [ 46 ]. Ag-phendione and Cu-phendione were able to bind to double-stranded DNA via hydrogen bonding, hydrophobic and electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Ag-phendione and Cu-phendione were able to bind to double-stranded DNA via hydrogen bonding, hydrophobic and electrostatic interactions. In addition, Cu-phendione was able to induce topoisomerase I mediated DNA relaxation of supercoiled plasmid DNA, in addition to inducing oxidative DNA injuries [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Ag(I) complexed to phen or a phen-type ligand (e.g., phendione) have presented with additional routes in which they exert their toxicity against microorganisms, such as interacting with double stranded DNA [ 36 ] or suppressing virulence [ 35 ]. Cu(II) and Mn(II)-phen complexes have been reported to be avid producers of ROS [ 112 ] which is thought to cause cell membrane damage and thiol depletion.…”
Section: Discussionmentioning
confidence: 99%
“…They were effective inhibitors of the metalloenzyme Elastase B (lasB), which is secreted by P. aeruginosa , suggesting this as a novel potential chemotherapeutic target [ 35 ]. Moreover, they were able to interact with double-stranded DNA and promote oxidative damage, suggesting multiple mechanisms of action in P. aeruginosa [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the use of metal complexes associated with repurposed/novel drugs is a new line of research that is gaining attention, since many of these compounds can be bactericidal, fungicidal, and even present antiparasitic action [ 13 , 14 , 15 , 16 , 17 , 18 ]. In this sense, a previous study from our group showed that two aminopyridine derivatives complexed with Cu 2+ , namely, cis -aquadichloro( N -[4-(hydroxyphenyl)methyl]-2-pyridinemethamino)copper ( 3a ) and its glycosylated ligand cis -dichloro( N -{[4-(2,3,4,6-tetra- O -acetyl-β-D-glucopyranosyloxy)pheny]lmethyl}-2-pyridinemethamino)copper ( 3b ), were effective against the infective form (trypomastigote) of T. cruzi , while non-toxic action was reported for RAW macrophages [ 19 ].…”
Section: Introductionmentioning
confidence: 99%